Complex Survey of the Argentine Islands and Galindez Island (Maritime Antarctic) as a Research Area for Studying the Dynamics of Terrestrial Vegetation - Parnikoza, I.; Berezkina, A.; Moiseyenko, Y.; Malanchuk, V.; Kunakh, V. (Ukrainian Antarctic Journal, 2018)
The aim of this research was generalization of base information about study area – Argentine Islands and detail characteristic of terrestrial biotopes by description and mapping of landscape elements, surface waters, and general vegetation for the chosen monitoring area of Galindez Island realized during the seasons of 2014, 2016, 2017. We also characterized animal and anthropogenic effects on the distribution of the different vegetation types. In this research a number of methods of field investigation and mapping with ArcGIS is used. Results. It was shown that most types of the available vegetation are predominantly distributed on those landscape elements, which rise above the permanent snow level, as well as get free from the snow the earliest during the summer, or they are not covered with snow in the winter. Various vegetation types can be formed here from the most sensitive to the duration of the vegetative period, e.g. communities with vascular plants, to the most tolerant to prolonged staying under snow, e.g. crustose lichens. This effect depends on the height and the sunlight availability, the duration of snow-free period on it, as well as humidity, the distance from the sea and the flow of organic matter from the sea birds. At present, in the area of the Argentine Islands in general, and on the Galindez Island in particular, the expansion of Pygoscelis papua (Spheniscidae) is observed, which has already led to the degradation of typical vegetation types in the area where these colonies had originated. The limited input of organic matter from the seabirds contributes to the development of moderately nitrophilic groups, whereas the use of these plants and lichens as the nest material leads to the distribution of vegetation in the region. The largest anthropogenic transformation occurred in the area when the station complex was built. At present, the populations of Deschampsia antarctica (Poaceae) are being formed in the area, shielded by the construction elements, which also contribute to the recolonization of certain species of scalloped lichens, but only on oldest constructions of Вritish period 1954—1996. Conclusions. It’s necessary: to continuation of monitoring of the influence of natural and anthropogenic factors on vegetation of the region; Limitation of the scientific collection of rare species, in particular Colobanthus quitensis (Caryophyllaceae); Creation of new nature protected areas with a regime of strict protection (Ia IUCN) based on the allocation of sites with the highest biodiversity valuable for monitoring in non-intervention; Additional explanatory activity on the value and vulnerability of the terrestrial ecosystems in the region.